Purification and characterization of a flavonol 3-O-beta-heterodisaccharidase from the dried herb of Fagopyrum esculentum Moench. - Baumgertel, Andreas; Grimm, Rudi; Eisenbeiß, Wilhelm Friedrich; Kreis, Wolfgang (Phytochemistry, 2003)
A flavonol-3-O-β-heterodisaccharide glycosidase (FHG I) was isolated from dried aerial tissues of Fagopyrum esculentum Moench (Fagopyri herba). It has a specific enzyme activity of ca. 3.5 nkat mg-1 protein in buffered extracts when rutin (quercetin-3-O-rutinoside) was used as substrate and an optimal enzyme activity was seen at around pH 4.8 and 30 °C. FHG I was purified about 156-fold to apparent homogeneity by hydrophobic interaction, anion exchange and size exclusion chromatographic steps. The apparent molecular mass of FHG I was 74.5 ± 2 kDa as determined by SDS-PAGE and it is a monomeric glycoprotein with a carbohydrate content of 23%. The isoelectric point as determined by isoelectric focusing was 5.7 and the energy of activation was 32 kJ mol-1. FHG I exhibits a high substrate specificity, preferring flavonol 3-O-glycosides comprising the disaccharide rutinose. The Km and Vmax values for the natural substrate rutin were calculated to be 0.561 μM and 745 nkat mg -1 protein, respectively. Two oligopeptide fragments obtained after enzymatic digestion of FHG I were sequenced and showed similarities to sequences of β-glucohydrolases from other plant species. Polyclonal antibodies were raised and their specificities determined. Another flavonol 3-O-β -heterodisaccharide glycosidase (FHG II) could also be detected in buckwheat herb, having a molecular mass of 85.3 ± 2 kDa and an isoelectric point between pH 6.0 and 6.5. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dbio.LPB.purifi
Keywords: β-Glycosidase; Fagopyrum esculentum; Polygonaceae; Purification; Rutin; Rutinoside